2017
DOI: 10.1016/j.cortex.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Control adjustments in speaking: Electrophysiology of the Gratton effect in picture naming

Abstract: Accumulating evidence suggests that spoken word production requires different amounts of top-down control depending on the prevailing circumstances. For example, during Stroop-like tasks, the interference in response time (RT) is typically larger following congruent trials than following incongruent trials. This effect is called the Gratton effect, and has been taken to reflect top-down control adjustments based on the previous trial type. Such control adjustments have been studied extensively in Stroop and Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
(99 reference statements)
4
26
0
Order By: Relevance
“…Since congruent trials in Stroop map onto the same representation, while incongruent trials map onto two different representations, the general pattern of N450 matches the N400-like effects in PWI studies with identity vs. semantic distractors (Piai et al, 2012;Shitova et al, 2017): The addition of a new representation (the non-identity distractor) induces more negativity on N450 and the ERPs observed within the N400 window in PWI, blocked cyclic and continuous naming paradigms, suggesting a possible common origin.…”
Section: Monitoring and Controlsupporting
confidence: 55%
See 1 more Smart Citation
“…Since congruent trials in Stroop map onto the same representation, while incongruent trials map onto two different representations, the general pattern of N450 matches the N400-like effects in PWI studies with identity vs. semantic distractors (Piai et al, 2012;Shitova et al, 2017): The addition of a new representation (the non-identity distractor) induces more negativity on N450 and the ERPs observed within the N400 window in PWI, blocked cyclic and continuous naming paradigms, suggesting a possible common origin.…”
Section: Monitoring and Controlsupporting
confidence: 55%
“…Compared to the early window, the findings in the N400 window have been reported more uniformly. PWI studies that compared semantically related to identity distractors have found more negative waveforms in the N400 time window for the semantically related distractors (Piai, Roelofs, & van der Meij, 2012;Shitova, Roelofs, Schriefers, Bastiaansen, & Schoffelen, 2017). It is important to note that the "identity" distractor does not activate a separate representation from that of the target.…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…Despite various explanations, all agree that this effect (often called conflict adaptation) reflects dynamic reactive control, once stimulus-repetition and learning confounds are removed (Duthoo & Notebaert, 2012). Similar adaptation patterns have emerged in production using a Picture-Word Interference (PWI) task Shitova, Roelofs, Schriefers, Bastiaansen, & Schoffelen, 2017), when individuals must name images (e.g., truck) despite a semantically distracting word superimposed on it (e.g., car). This finding suggests that, similar to nonverbal tasks, language production is regulated in real time via a monitoring-control loop.…”
Section: Forward Models Of Monitoringmentioning
confidence: 90%
“…However, language production often involves cognitive control 1 . For instance, many behavioral and neuroimaging studies have demonstrated that language production involves conflict monitoring and control (Freund, Gordon, & Nozari, 2016; Gauvin, De Baene, Brass, & Hartsuiker, 2016; Hanley, Cortis, Budd, & Nozari, 2016; Nozari, Dell, & Schwartz, 2011; Nozari & Novick, 2017; Riès, Janssen, Dufau, Alario, & Burle, 2011; Shitova, Roelofs, Schriefers, Bastiaansen, & Schoffelen, 2017; Van Maanen & Van Rijn, 2010), engaging language related regions such as left middle temporal cortex (de Zubicaray, McMahon, & Howard, 2015; de Zubicaray, Wilson, McMahon, & Muthiah, 2001) and domain general regions such as pre supplementary motor area, anterior cingulate, and ventrolateral prefrontal cortex (Nozari & Novick, 2017). Language production also involves inhibitory control (Shao, Meyer, & Roelofs, 2013; Shao, Roelofs, Acheson, & Meyer, 2014; Shao, Roelofs, & Meyer, 2012; Tydgat, Diependaele, Hartsuiker, & Pickering, 2012; Tydgat, Stevens, Hartsuiker, & Pickering, 2011), and other types of control processes (Nozari, Freund, Breining, Rapp, & Gordon, 2016).…”
Section: Introductionmentioning
confidence: 99%